1993
DOI: 10.1007/bf00374295
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral contributions to control of heart rate during heat acclimation

Abstract: The contributions of the autonomic nervous system and the cardiac pacing cells in the development of heat-acclimation-induced bradycardia were analyzed, and the effect of heat acclimation on the chronotropic response of the heart to heat stress (40 degrees C) was studied. Rats were acclimated at 34 degrees C for 0, 5, 14, 30 and 60 days. Heart rate (HR) was measured in conscious animals, using chronic subcutaneous electrodes. Sympathetic and parasympathetic influences were studied by IP administration of 0.1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 16 publications
3
40
0
1
Order By: Relevance
“…The C group was held at an ambient temperature of 24 Ϯ 1°C; heat acclimation was attained by a continuous exposure to 34 Ϯ 1°C and 30 -40% relative humidity in a light-cycled room (12:12 h) for 30 days (long-term acclimation), as previously described (15). The efficacy of this treatment has been previously validated using the decrease in heart rate as a criterion (18). For characterization of the effects of HS on C and AC rats, the animals were subjected to HS at 41°C for 2 h. During HS, the colonic temperature (T c) was monitored online, using a YL 402 thermistor inserted 6 cm beyond the anal sphincter and attached to a computerized data acquisition system.…”
Section: Methodsmentioning
confidence: 99%
“…The C group was held at an ambient temperature of 24 Ϯ 1°C; heat acclimation was attained by a continuous exposure to 34 Ϯ 1°C and 30 -40% relative humidity in a light-cycled room (12:12 h) for 30 days (long-term acclimation), as previously described (15). The efficacy of this treatment has been previously validated using the decrease in heart rate as a criterion (18). For characterization of the effects of HS on C and AC rats, the animals were subjected to HS at 41°C for 2 h. During HS, the colonic temperature (T c) was monitored online, using a YL 402 thermistor inserted 6 cm beyond the anal sphincter and attached to a computerized data acquisition system.…”
Section: Methodsmentioning
confidence: 99%
“…Horowitz and Meiri [7] have previously demonstrated that the decreased HR seen with heat acclimation is in part a function of acceleration of parasympathetic and withdrawal of sympathetic nervous input. In previous work with spectral analysis of HRV, high frequency peaks and the power represented by the area under the curve of the high frequency peak have been used as an indication of parasympathetic activity, and the ratio of low to high frequency power has been used as an indication of sympathetic activity [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is individual variability in heat tolerance and ability to acclimate, the following are among the physiological changes generally observed with acclimation in both man [16] and rats [4,6,7,8] There is an increase in plasma volume, tolerance time in the heat, skin blood flow, time interval during which sweating (saliva spreading in rats) can be maintained; there is a decrease in basal heart rate (HR) and HR during heat exposure, core temperature (Tc) during heat exposure, and Tc threshold for sweating (in terms of salivation).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations